2013
DOI: 10.1175/jas-d-12-0346.1
|View full text |Cite
|
Sign up to set email alerts
|

Compensation between Resolved and Unresolved Wave Driving in the Stratosphere: Implications for Downward Control

Abstract: Perturbations to the orographic gravity wave parameterization scheme in an idealized general circulation model reveal a remarkable degree of compensation between the parameterized and the resolved wave driving: when the orographic gravity wave driving is changed, the resolved wave driving tends to change in the opposite direction, so there is little impact on the Brewer–Dobson circulation. Building upon earlier observations of such compensation, an analysis based on quasigeostrophic theory suggests that the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
87
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 39 publications
12
87
2
Order By: Relevance
“…Recently, some studies revealed possible compensation of PW drag of the middle atmospheric circulation by parameterized OGWs in general circulation models (McLandress and McFarlane 1993;Cohen et al 2013Cohen et al , 2014Sigmond and Shepherd 2014;Watson and Gray 2015). Our results show that taking account of OGW parameterization can both decrease or increase wave amplitudes, EP-fluxes, and wave drag of the mean flow depending on the considered PW modes.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, some studies revealed possible compensation of PW drag of the middle atmospheric circulation by parameterized OGWs in general circulation models (McLandress and McFarlane 1993;Cohen et al 2013Cohen et al , 2014Sigmond and Shepherd 2014;Watson and Gray 2015). Our results show that taking account of OGW parameterization can both decrease or increase wave amplitudes, EP-fluxes, and wave drag of the mean flow depending on the considered PW modes.…”
Section: Discussionmentioning
confidence: 57%
“…However, this ratio differs largely between various models. Cohen et al (2013) suggest that due to compensation effects between the different wave types, the impact of the differences in gravity wave perturbation on the total circulation is reduced. Hence, models tend to agree more on the total strength of the circulation than on individual components.…”
Section: Model Characteristics That Can Influence Mixingmentioning
confidence: 99%
“…However, this ratio differs largely between various models. Cohen et al (2013) suggest that due to compensation effects between the different wave types, the impact of the differences in gravity wave perturbation on the total circulation is reduced.…”
mentioning
confidence: 99%